Relationship between Density and Mechanical Properties of Oil Palm Empty Fruit Bunch Cement Fibreboards after using Vibration Table during Fabrication - FONG, MENG CHAN; Nik Soh, Nik Mohd Zaini (Recent Trends in Civil Engineering and Built Environment, 2021)
Oil palm empty fruit bunch fibre has been studied for its applicability and potential replacement for wood fibres in producing cement fibreboards as Malaysia has abundant of these biomasses from the oil palm industry. Modification and method of improvement for the properties of empty fruit bunch cement fibreboard (EFBCB) was needed to match the properties of wood fibre cement board, and application of vibration table during the moulding process in the fabrication stage of EFBCB was introduced. This method applied the technique of compaction of concrete through vibration which was common in construction practices. A research was conducted to study the relationship between density and mechanical properties of EFBCB after using vibration table during fabrication. 18 samples were fabricated from 3 cement: EFB fibre ratio of 2:1, 2.5:1 and 3:1, of which 9 samples applied vibration and the other 9 were manually hand formed. Results shown that vibration table has effect on the density distribution across the EFBCB samples, which the density across the board are more evenly and uniformly distributed, however difference of average density between hand plus vibration table formed (HF+VT) EFBCB with hand formed (HF) EFBCB was not significant. The mechanical properties of HF+VT EFBCB increased compared to HF EFBCB. HF+VT EFBCB of ratio 3:1 possess the highest mechanical properties values (MOE 4888 N/mm2, MOR 11.40 N/mm2, IB 0.37 N/mm2). Hence, applying vibration table can be regarded as a new and effective method to improve the qualities and properties of EFBCB.